2022
DOI: 10.2147/jir.s349572
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Mesenchymal Stem Cells on Secondary Inflammation in Spinal Cord Injury

et al.

Abstract: Spinal cord injury (SCI) is a catastrophic condition with high morbidity and mortality that still lacks effective therapeutic strategies. It is well known that the most important stage in SCI pathogenesis is secondary injury, and among the involved mechanisms, the inflammatory cascade is the main contributor and directly influences neurological function recovery. In recent years, increasing evidence has shown that mesenchymal stem cells (MSCs) transplantation is a promising immunomodulatory strategy. Transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 199 publications
(232 reference statements)
0
12
0
Order By: Relevance
“…Cytokines secreted by strong inflammation-induced reactive astrocytes form glial scars, which causes secondary damage that is detrimental to SCI function recovery. 79 We showed that inflammation was reduced by decreasing cell debris and reactive astrocytes, which play an important role in the damage through a series of processes that cause secondary damage and functional recovery. Therefore, we measured the inflammatory reaction in each transplant group after the pathological response.…”
Section: Resultsmentioning
confidence: 96%
“…Cytokines secreted by strong inflammation-induced reactive astrocytes form glial scars, which causes secondary damage that is detrimental to SCI function recovery. 79 We showed that inflammation was reduced by decreasing cell debris and reactive astrocytes, which play an important role in the damage through a series of processes that cause secondary damage and functional recovery. Therefore, we measured the inflammatory reaction in each transplant group after the pathological response.…”
Section: Resultsmentioning
confidence: 96%
“…In addition to their ability to differentiate into different cell types, MSCs also play a regulatory role in inflammatory and immune responses. Many studies have shown that after cell or tissue injury, MSCs can be activated by inflammatory cytokines and control the process of tissue regeneration by releasing a series of factors that may promote the differentiation and proliferation of progenitor cells while participating in immune regulation and inhibiting inflammatory responses ( 67 , 183 , 184 ). ( Figure 2 ).…”
Section: Mscs and Stem Cellsmentioning
confidence: 99%
“…On the other hand, a large number of investigations have shown the promising therapeutic effect of MSCs in CNS disorders, such as SCI, stroke, epilepsy, Alzheimer's disease, Parkinson's disease, and depression 20,85,93–96 . Indeed, due to such MSCs properties as renewal, multipotent differentiation, and, most significantly, anti‐inflammatory capabilities, they have been considered the ideal agents for this purpose 97 .…”
Section: Mesenchymal Stem Cells and Msc‐derived Exosomes Regulate Neu...mentioning
confidence: 99%